970 FRAILTY IS INVERSELY CORRELATED WITH SERUM ALBUMIN IN ACUTE HIP FRACTURE. (14th June 2022) - Pathmanathan, K; Mubin, M; Sevilla, C; Zaman, M; Chan, R; Hussain, M; Brown, E; McDevitt, G; Khan, R; Nandi, A; Mukherjee, B; Obiechina, N
Abstract: Introduction: Frailty and sarcopenia have been shown to significantly increase the risk of falls, traumatic hip fractures and all-cause mortality in the elderly. The assessment of frailty using a validated clinical frailty scale such as that proposed by Rockwood et al., therefore, continues to remain an important step in determining post-operative prognosis in patients undergoing hip fracture surgery. The purpose of this study was to examine the relationship between frailty and serum albumin—an independent biochemical predictor of survival in hip fracture patients (1). Method: This retrospective cross-sectional study analysed 190 patients, aged above 60 years, admitted to Queen's Hospital Burton (QHB) between the 1st January and 28th December 2019 with a newly diagnosed hip fracture. Pre-operative serum albumin levels (g/L) and Rockwood clinical frailty scores (rCFS) were recorded from electronic medical records (EMR). Using the SPSS 27 statistical package, Pearson's correlation co-efficient and linear regression analysis were carried out using these variables. Results: A total of 190 patients were included in the study (57 male, 133 female). Mean patient age was 82.2 ± 8.47 years. More than 50% of patients had a Rockwood CFS ≥5. Mean serum albumin (g/L) was 37.3 ± 6.56. A statistically significant inverse correlation was demonstrated between pre-operative serum albumin levels and Rockwood CFS (r = −0.243, p < 0.001). Conclusion: This study showed how serum albumin, a negative acute phase reactant and marker of chronic malnutrition, is inversely associated with frailty in hip fracture patients and the important role of Rockwood CFS and pre-operative serum albumin levels in the prognostication of hip fractures in the elderly. References 1) Bohl D, Shen M, Hannon C, Fillingham Y, Darrith B, Della Valle C. Serum Albumin Predicts Survival and Postoperative Course Following Surgery for Geriatric Hip Fracture. Journal of Bone and Joint Surgery. 2017;99(24):2110–2, 118.